(untitled) - Heritage Moleke (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Covid-19 pandemic stunned not only health arena but also the educational system in which educational stakeholders as well as practitioners were obligated to strategise for new procedures to fulfil educational objectives. In this regard, face to face teaching and learning transited to online, asynchronous education, which is challenging and even more challenging to students with special needs. These students really on assistive devices for academic success of which it becomes difficult for them to succeed academically without these devices. Several scholars in the literature contended that there is still a gap with regard to educational resources for students with special needs. For this reason, this study tends to examine the availability and effectiveness of assistive devices for educational success of blind students in the days of covid-19 pandemic. By examining these special devices, this study will contribute towards the existing knowledge gap about the needs of students with special needs which will further assist the institutions of higher education as well as the educational stakeholders to innovate their services for academic success of the students with special needs. The study adopted a qualitative descriptive design. Data was collected through interviews and analysed by using Qualitative Content Analysis (QCA). The findings were presented and analysed based on the study objectives and the recommendations were made.